تعليم اللغة العربية وتعلّمها وإمكاناتها لدى الجيل الرقمي في إندونيسيا - نور, مولدية أحمد; أتانجواني, إيفي ستياواتي; سوليساياه, ايرني (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3638, 2025)
This study explores the teaching and learning of Arabic among digital natives within the Indonesian higher education context, focusing on UIN Maulana Malik Ibrahim Malang. The research highlights the importance of adapting Arabic language pedagogy to meet the cognitive and technological characteristics of the digital generation. By analyzing the university’s language policy, the study identifies institutional strengths and challenges in implementing technology-enhanced Arabic learning. Based on recent research (2018–2024), it proposes an interactive pedagogical model grounded in blended learning, integrating face-to-face, digital, and task-based approaches. The proposed model aims to foster communicative competence, learner autonomy, and digital literacy among Arabic learners. The paper concludes that the successful adoption of blended learning requires continuous faculty training, the development of culturally relevant digital content, and systematic policy evaluation to align with Indonesia’s digital transformation in education.